Does agency cost model explain business fluctuations in Japan? An empirical attempt to estimate agency cost by firm size - Kazuo Ogawa; Hirokuni Uchiyama (Osaka University, Institute of Social and Economic Research (ISER), 2003)
An attempt is made to estimate a state space model of investment and borrowing in a Bayesian framework and extract the unobservable agency cost of Japanese firms by firm size. Our estimates of the agency cost exhibited a declining trend in the late 80s and then switched to an increasing trend in the 90s. We pin down the driving force of agency cost to be the market value of land. Furthermore, we find that investment and borrowing behavior of small firms is very much affected by their agency cost in the late 80s and the 90s. Our evidence demonstrates that imperfection of capital market is notable for small firms in Japan.
Keywords: C51; E22; E44; E51; 330; Agency cost; Investment; Collateral; Land; Borrowing; State space model; Kalman filter; Gibbs sampling; Kapitalkosten; Transaktionskosten; Betriebsgröße; Japan; Zustandsraummodell